Recent Advances in Electrocatalysts for Carbon Dioxide Reduction - Deng Xiaojie; Huang Ziying; Wu Xuheng (E3S Web of Conferences)
With the progress of science and technology and the economy, realizing “sustainable development” has become the common development goal of many countries and regions in the world today. Carbon dioxide (CO2) is widely used as an important carbon resource, which aggravates the problem of global warming. electrocatalytic Carbon Dioxide reduction reaction (ECO2RR) is a key technology for converting CO2 into useful carbon-based products (such as C2H4, CO, CH3OH). Thereby increasing the economic and commercial value of clean energy worldwide. In this paper, different electrocatalysts commonly used in ECO2RR reactions were studied. By summarizing the definition, characteristics, deficiencies, and modification strategies of different electrocatalysts, different effects of different electrocatalysts on ECO2RR reaction were studied. This paper helps to make up for the shortage of different electrocatalysts in the literature review of ECO2RR reaction, promote the development of ECO2RR reaction electrocatalysts, and promote the progress of ECO2RR reaction. Let the ECO2RR reaction enable energy conservation and emission reduction, and provide more effective measures for the early realization of the “double carbon goal”. Due to the limited literature on electrocatalysts, the current research is not comprehensive. Future studies should summarize the characteristics of different electrocatalysts in ECO2RR reactions more comprehensively.